Neuronal expression of CB2 cannabinoid receptor mRNAs in the mouse hippocampus. (17th December 2015) - Li, Y.; Kim, J.
Highlights: Hippocampal excitatory and inhibitory neurons in mice express CB2R mRNAs. Only a subset of hippocampal neurons express CB2 cannabinoid receptor mRNAs. Levels of hippocampal CB2R mRNAs are stable during postnatal development. The expression of CB2 cannabinoid receptor mRNAs is augmented in cultured tissue. Abstract: In the brain, CB1 cannabinoid receptors primarily mediate the effects of cannabinoids, but CB2 cannabinoid receptors (CB2Rs) have recently been discovered in the nervous system and also implicated in neuromodulatory roles. To understand the mechanisms of CB2R functions in the brain, it is essential to localize CB2Rs, but the types of cells expressing CB2Rs have been controversial. Unequivocal localization of CB2Rs in the brain has been impeded in part by the low expression levels of CB2Rs and poor specificity of detection methods. Here, we used an ultrasensitive and specific in situ hybridization method called the RNAscope to determine the spatial pattern of CB2R mRNA expression in the mouse hippocampus. CB2R mRNAs were mostly expressed in a subset of excitatory and inhibitory neurons in the CA1, CA3 and dentate gyrus areas, but rarely in microglia. CB2R knock-out mice were used as a negative control. Using the quantitative real-time polymerase chain reaction, we also found that the temporal pattern of CB2R mRNA expression was stable during postnatal development. Consistent with previous reports, the immunological detection of CB2Rs was not reliable, implying extremely low levels of the protein expression and/or insufficient specificity of the current anti-CB2R antibodies. Our findings of the expression patterns of CB2R mRNAs may help determine the cell types involved in, and hence the mechanisms of, the CB2R-mediated neuromodulation.